2019 novel coronavirus of pneumonia in Wuhan, China: emerging attack and management strategies. Issue 1 (20th February 2020) - She, Jun; Jiang, Jinjun; Ye, Ling; Hu, Lijuan; Bai, Chunxue; Song, Yuanlin
Abstract: An ongoing outbreak of 2019‐nCoV pneumonia was first identified in Wuhan, Hubei province, China at the end of 2019. With the spread of the new coronavirus accelerating, person‐to‐person transmission in family homes or hospitals, and intercity spread of 2019‐nCoV occurred. At least 40, 261 cases confirmed, 23, 589 cases suspected, 909 cases death and 3444 cases cured in China and worldwide 24 countries confirmed 383 cases being diagnosed, 1 case death in February 10th, 2020. At present, the mortality of 2019‐nCoV in China is 2.3%, compared with 9.6% of SARS and 34.4% of MERS reported by WHO. It seems the new virus is not as fatal as many people thought. Chinese authorities improved surveillance network, made the laboratory be able to recognize the outbreak within a few weeks and announced the virus genome that provide efficient epidemiological control. More comprehensive information is required to understand 2019‐nCoV feature, the epidemiology of origin and spreading, and the clinical phenomina. According to the current status, blocking transmission, isolation, protection, and alternative medication are the urgent management strategies against 2019‐nCoV.